PERMASALAHAN ANTENATAL CARE (ANC) PADA KEHAMILAN REMAJA DI WILAYAH PUSKESMAS KARANGLEWAS KABUPATEN BANYUMAS - Trisnawati, Yuli; Khosidah, Amik (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Teenage pregnancy have a higher risk, not only damage the future of teenagers are concerned but also very dangerous for the health of adolescents. Antenatal Care (ANC) is a planned program of observation, education, and medical treatent in pregnant woman. ANC purpose in to monitor the progress of pregnancy, ensuring health and infant growth and development as well as improving and maintaining physical, mental, and social mother and baby. Antenatal Care behavior is determined by several factors, including predisposing factor, enabling factor, and reinforcing factor.To analyze the determinants of antenatal care on behavior of teenage pregnancy in the region Karanglewas health center Banyumas Residence 2014.The kind of reaserch is descriptive analytic with cross sectional approach. Taking into 43 teenage pregnancy third trimester. The sample taking technique used total sampling method. The analyze used the chi square and logistic regression. The majority education of teenage pregnant is elementary education (81.4%). The majority knowledge of teenage pregnant is good (60.5%). The majority attitude of teenage pregnancy motherâ€™s is good (60.5%). The majority behavior of teenage pregnancy is goodÂ  (81.4%). There is no correlation between education and behavior of Antenatal Care (p = 0,623 > = 0,05). There is a correlation between knowledge and behavior of Antenatal Care (p = 0,042 < = 0,05). There is a correlation between attitude and behavior of Antenatal Care (p = 0,042 < = 0,05). And the most factor that influence ANC behavior are knowledge and attitude (OR = 0,018). Keyword : Education, knowledge, attitude, behavior of ANC